Survey of Australian listed companies reporting on the Internet : a comparison between service and non service industries. - Cheong, Zheng Mun. (2008)
With the increasing use of the Internet, especially since the development of the World Wide Web, more companies have found this relatively new communication medium a good way to provide information to various stakeholders. In our research, we attempt to understand the disclosure status of Australian listed companies with web sites. In particular, we are trying to ascertain if there is any difference in the level of corporate disclosure between companies in the service and non-service industries.